2009
DOI: 10.1007/s00425-009-1040-1
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of HMW-GS sequence variation through somatic hybridization between Agropyron elongatum and common wheat

Abstract: A symmetric somatic hybridization was performed to combine the protoplasts of tall wheatgrass (Agropyron elongatum) and bread wheat (Triticum aestivum). Fertile regenerants were obtained which were morphologically similar to tall wheatgrass, but which contained some introgression segments from wheat. An SDS-PAGE analysis showed that a number of non-parental high-molecular weight glutenin subunits (HMW-GS) were present in the symmetric somatic hybridization derivatives. These sequences were amplified, cloned an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…As the most abundant repetitive sequences in wheat genome, the retrotransposon-related sequences showed high frequency of alteration (6.5%) in the introgression lines (Table 4). Similarly, high-frequency sequence variation through indels of repetitive motifs (14/37, 37.8%) was also observed in the glutenin gene family (Feng et al 2004;Liu et al 2007Liu et al , 2009Gao et al 2010). This supports the notion that repetitive sequences are a driving force behind the de novo genetic variation generated in the introgression lines.…”
Section: Genetic Alterations Driven By Repetitive Sequencessupporting
confidence: 73%
See 1 more Smart Citation
“…As the most abundant repetitive sequences in wheat genome, the retrotransposon-related sequences showed high frequency of alteration (6.5%) in the introgression lines (Table 4). Similarly, high-frequency sequence variation through indels of repetitive motifs (14/37, 37.8%) was also observed in the glutenin gene family (Feng et al 2004;Liu et al 2007Liu et al , 2009Gao et al 2010). This supports the notion that repetitive sequences are a driving force behind the de novo genetic variation generated in the introgression lines.…”
Section: Genetic Alterations Driven By Repetitive Sequencessupporting
confidence: 73%
“…DNA comparison of a well-characterized set of glutenin proteins among parents and derivatives shows that all novel glutenin genes in hybrid progenies originated from alien genes of tall wheatgrass and allelic variation of parent wheat genes (Liu et al 2007. Such de novo alleles do not arise simply as a result of UV-induced mutagenesis, as high frequency of the glutenin alleles were also found in symmetric somatic hybrids without UV pretreatment (Gao et al 2010). Moreover, somaclonal variation of parent wheat is too rare to account for the observed high frequency of novel glutenin alleles in the somatic hybrids (Feng et al 2004).…”
mentioning
confidence: 99%
“…This response included both signal perception and adaptation to the stress. The ability to achieve this must have derived from genomic variation or expression alternation of wheat genes brought about by the somatic hybridization process used to introgress tall wheatgrass chromosome segments (Gao et al 2010). The origin of these differentially expressed genes and the effect of introgressed genetic materials on the regulation of wheat genes is worthy of being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis has shown that it carries a small number of short tall wheatgrass chromosome segments dispersed throughout its genome (Wang et al 2005;Chen and Xia 2003), and it is likely that some at least of its salinity tolerance is derived from the tall wheatgrass genes mapping to these segments (Peng et al 2009;Shan et al 2006). Comparisons between SR3 and JN177 have also revealed whole-scale changes at both the genetic and epigenetic level (Liu et al 2007(Liu et al , 2010, some of which, it is assumed, must be responsible for the enhanced salinity and drought tolerance of SR3. A proteomic analysis of seedlings subjected to salinity stress up to a level of 200 mM NaCl has suggested that the performance of SR3 reflects its more effective capacity to ensure osmotic and ionic homeostasis, its superior ability to remove toxic by-products, and its better potential to recover when the stress is alleviated (Peng et al 2009;Wang et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…It tolerates high levels of salt (600 mM NaCl) and drought stress and has an aggressive and vigorous cross-walk rhizome system that facilitates the absorption of moisture under high salt stress and drought conditions . Comparisons with wheat (Triticum aestivum), salt-tolerant tall wheatgrass (Agropyron elongatum) and asymmetric somatic hybrids between bread wheat and tall wheatgrass demonstrated an exceptional level of salinity tolerance, suggesting that the introgression of new genetic materials into the wheat genome induced genomic variation and regulated the expression of wheat genes to contribute to stress tolerance in the hybrids (Xia et al 2003, Gao et al 2010, Liu et al 2012. Furthermore, intergeneric hybrids of T. aestivum and Leymus demonstrated that the transfer of resistance genes from Leymus to wheat might result in wheat improvement Chen 1996, Larson et al 2012).…”
Section: Introductionmentioning
confidence: 99%